The Role of Artificial Intelligence in Telemedicine: Legal Considerations under Indonesian Health Laws - Sebastian, Rommy (Devotion : Journal of Research and Community Service, 2024)
The integration of Artificial Intelligence (AI) in Indonesia’s healthcare system, particularly in telemedicine, presents both opportunities and challenges. AI enhances healthcare delivery by improving diagnostics and patient management, especially in underserved areas. However, its adoption raises legal concerns, particularly around data privacy, security, and professional accountability. Indonesia's regulatory framework, including the Personal Data Protection Law (UU PDP) and Health Ministerial regulations, governs healthcare and data use but has not fully adapted to the complexities of AI. This study aims to analyse the adequacy of Indonesia’s legal framework in addressing the challenges posed by AI in telemedicine. A qualitative method was used, involving a comprehensive review of existing laws and case studies of AI application in healthcare both locally and globally. The results reveal that while Indonesian health laws provide a foundation for telemedicine regulation, they lack specific provisions for AI-related issues, such as algorithm transparency, liability for AI errors, and real-time data handling. The conclusion emphasizes the need for updated regulations that account for AI’s unique characteristics, ensuring that its benefits in healthcare are fully realized while protecting patient rights and aligning with international legal standards. This research highlights the importance of legal reform to create a safer, more efficient, and ethically sound AI-driven healthcare system in Indonesia.